Effects of Combination of Curcumin and Piperine Supplementation on Glycemic Profile in Patients with Prediabetes and Type 2 Diabetes Mellitus: A Systematic Review and Meta-analysis - Widjanarko, Nicolas Daniel; Tamio, Erich; Jusni, Louis Fabio Jonathan; Alvianto, Steven; Arifin, Erlangga Saputra; Iryaningrum, Maria Riastuti (Journal of the ASEAN Federation of Endocrine Societies, 2024)
Objective. This study aimed to evaluate the effects of combination of curcumin and piperine supplementation on Fasting Plasma Glucose (FPG), Homeostatic Model of Insulin Resistance (HOMA-IR), Body Mass Index (BMI) in patients with prediabetes and type 2 Diabetes Mellitus (T2DM). This review was done to identify potential herbal remedies that may help improve glycemic parameters, leading to better health outcomes in combination with current antidiabetic treatment. Methodology. This systematic review was based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). It was conducted in 2023 with sources and databases from MEDLINE, EBSCO-Host, ScienceDirect and ProQuest. This paper included randomized-controlled trials exploring the effects of the combination of curcumin and piperine on patients with prediabetes and T2DM. Systematic reviews, observational studies, case reports, case series, conference abstracts, book sections, commentaries/editorials, non-human studies and articles with unavailable full-text and written in non-English language, were excluded. The key terms for the literature search were “curcumin,” “piperine,” “prediabetes” and “Type 2 Diabetes Mellitus.” We use Cochrane Risk of Bias (RoB) 2 for quality assessment of the included studies and Review Manager (RevMan) 5.4 to do the meta-analysis. Results. A total of three studies were included in this systematic review. Two studies from Neta et al., and Cicero et al., showed no significant difference in HOMA-IR, BMI and FPG levels between the curcumin, piperine and placebo groups. One study from Panahi et al. demonstrated a significant difference in BMI levels between the curcumin and piperine and placebo groups (p <0.01). The meta-analysis showed that FPG levels, HOMA-IR and BMI improved among patients with diabetes given in curcumin and piperine with reported mean differences (MD) of = -7.61, 95% CI [-15.26, 0.03], p = 0.05, MD = -0.36, 95% CI [-0.77 to 0.05], p = 0.09, and MD = -0.41, 95% CI [-0.85 to 0.03], p = 0.07, respectively). Conclusions. The supplementation of curcumin and piperine showed a numerical reduction in FPG, HOMA-IR and BMI, but were not statistically significant. Further research is needed as there is a paucity of studies included in the review.